Renaşterea filologiei - Alexandru Gafton (Revista de Istorie și Teorie Literară)
This text is not the result of a research endeavour on certain topics in philology, but rather the outcome of an extended reflection process on the general status of Romanian philology. For this reason, the issues we discuss have a general character and are concerned with Romanian philology on the whole, with its problems and tribulations, with the hardships it is being subjected to, and with the possible solutions for restoring the natural rights of a science that plays the role of a high-precision instrument, which guarantees the accuracy of any subsequent processing and interpretation of written material.